Ethnē Thrakōn in ancient greek and latin authors – what’s in a name? (Research Announcements "Heritage BG", 2025)
Writing l’histoire des noms, et même l’histoire par les noms is, in the case of Thracian ethnonyms, a particularly complex procedure. After briefly commenting on some of the difficulties, the present communication focuses on two specific cases attested in both literary and epigraphic sources (Sapaioi, Coelaletae) and, by analyzing variations in the attested forms of these ethnonyms, tries to differentiate between variations that can be considered pertinent to the history of the tribes from variations that can be attributed solely to the literary tradition. References:Delev, P. (2014). Istoriya na plemena v Yugozapadna Trakiya prez I h. pr. Hr.. Sofia.Fol, A., Spiridonov, T. (1983). Istoricheska geografiya na trakiyskite plemena do III v. pr. n.e.. Sofia.Tacheva, M. (2004) Etnonimat koylaleti i strategiyata Koyletike: istoriko-geografsko prouchvane. In: Vlast i sotsium v rimska Trakiya i Miziya. Vol. II, Sofia, 116-131.Venedikov, I. (1982). Traliykata toponimiya v dvizhenie. Naselenieto na Yugoiztochna Trakiya. In: Trakiyski Pametnitsi (ed. A. Fol). Vol. 3, Sofia, 32-170.Briscoe, J. (2012). A Commentary on Livy, Books 41-45. Oxford.Chryssanthaki-Nagle, K. (2007). L’histoire monétaire d’Abdère en Thrace (vie s. avant J.-C. - ne s. après J.-C.). Meletemata 51. Athens.Delev, P. (2018). The Romans in the Balkans and the Communities of the Thracian Interior. Actions and Reactions (2nd-1st C. BC). In: Les communautés du Nord Égéen au temps de l’hégémonie romaine. Entre ruptures et continuités (eds. J. Fournier, M.-G. G. Parissaki). Meletemata 77, Athens, 19-27.Detschew, D. (1976). Die thrakischen Sprachreste. Vienna, 2nd ed.Hatzopoulos, M. (2000). “L’histoire par les noms” in Macedonia. In: Greek Personal Names. Their Value as Evidence (eds. S. Hornblower, E. Matthews). Oxford University Press, Oxford, 99-117.Lenk, B. (1936). Die thrakischen Stämme (s.v. Thrake). In: RE VI A,1. Stuttgart, 404-407.LGPN: The Lexicon of Greek Personal Names, Vol. I-VC (1987-2018). Oxford.Ouhlen, J. (1992). Les théarodoques de Delphes. PhD Dissertation, University of Paris X, Nanterre. Unpublished.Papazoglou, F. (1988). Les villes de Macédoine l’époque romaine, BCH Suppl. No. 16. Athens.Parissaki, M.-G. (2024). Ethni Thrakon sti Thraki tou Aigaiou kata tous ellinistikous kai romaikous chronous II. Sapaioi kai Sapaiki. Tekmeria, No. 18, 1-66.Paunov, E. (2021). An enigmatic Thracian king and his coinage. In: Nunc decet caput impedire myrto. Studies Dedicated to Professor Piotr Dyczek on the Occasion of His 65th Birthday (eds. K. Narloch, T. Plyciennik, J. Żelazowski). Warsaw, 157-161.Plassart, A. (1921). Inscriptions de Delphes. La liste des Théorodoques. Bulletin de Correspondance Hellénique, No. 45, 1-85.Radt, S. (2002-2011). Strabons Geographika. Mit Übersetzung und Kommentar. Band 1-10. Göttingen.RDGE: Sherk, R. K. (1969). Roman Documents from the Greek East. Senatus Consulta and Epistulae to the Age of Augustus. Baltimore.Robert, L. (1962-1963). Eulaios, istoria kai anthroponymia. Epistimoniki Epetiris Filosofikis Scholis Panepistimiou Athinon 1962-1963, 519-529.Rufin Solas, A. (2020). Pre-Roman Bessoi. In: The Bessi in the Roman Empire (eds. I. Topalilov, S. Nedelcheva). Studia Academica Sumenensia 7, Shumen University Press, 24-37.Tomaschek, W. (1893). Die alten Thraker. Eine ethnologische Untersuchung. Sitzungsberichte der Kaiserlichen Akademie der Wissenschaften 128/4. Vienna, 1-130.
Keywords: Thracian ethnonyms; Sapaioi; Coelaletae